Sedentary behavior time as a predictor of hemoglobin A1c among adults, 40 to 59 years of age, living in the United States: National Health and Nutrition Examination Survey 2003 to 2004 and 2013 to 2014. Issue 4 (December 2019) - Nicolo, Michele L; Shewokis, Patricia A; Boullata, Joseph; Sukumar, Deeptha; Smith, Sinclair; Compher, Charlene; Volpe, Stella L
Background: Sedentary behavior activities have been associated with an increased risk of type 2 diabetes. Aim: Our aim was to determine whether sedentary behavior time (SBT) is predictive of hemoglobin A1c (HbA1c) ≥ 6.5% (48 mmol/mol). Methods: We used cross-sectional data, adults 40 to 59 years of age, from the National Health and Nutrition Examination Survey (NHANES) for 2003 to 2004 and 2013 to 2014. Responses to questions on the Physical Activity Questionnaire regarding time watching television/videos, and time spent sitting in front of a computer per day were compiled into tertiles. Binary logistic regression analysis was used to determine whether SBT was a predictor of a HbA1c ≥ 6.5% adjusting for age, sex, race and ethnicity, and body mass index. Results: In a univariate model, adults reporting ≥ 8 hours of SBT in NHANES 2003–2004 had 2.02 increased odds of a HbA1c ≥ 6.5% (OR = 2.02, 95% CI: 1.31, 3.13, p < 0.0001) compared to adults reporting ≤ 3 hours. After adjusting the regression model for age, sex, race and ethnicity, and body mass index, adults reporting ≥ 8 hours of SBT in NHANES 2003 to 2004 had 1.72 increased odds of HbA1c ≥ 6.5% (OR = 2.02, 95% CI: 1.10, 2.68, p < 0.0001) compared to adults reporting ≤ 3 hours of SBT. Reported SBT was not a predictor of HbA1c ≥ 6.5% for NHANES 2013 to 2014. Conclusion: Reported SBT was a predictor of HbA1c ≥ 6.5% among adults, 40 to 59 years of age, in NHANES 2003 to 2004, but was not a predictor in 2013 to 2014.